Theory and Practices Gap of Teacher Education Programs in Formal and Distance Education System: Shaista Anjum, Nasir Mahmood (PJDOL, 2023)
In Pakistan, a large number of prospective teachers are being trained frequently from formal and distance mode of education. The recent focus of the research was on pedagogical knowledge and practices of prospective teachers in distance and formal learning system of education. The purposed study was aimed to find out the comparison of pedagogical knowledge and practices of the prospective teachers in distance and formal education programs. The main objectives of the study were to explore the theoretical knowledge and to examine the pedagogical practices of prospective teachers in both mode of education. The study was quantitative and descriptive in nature. A survey was conducted through knowledge based test which was drawn from Higher EducationCommission courses outline of B.Ed (Hons) and ADE programs on (408) prospective teachers.